Contexts, mediations and production of meanings: a conceptual and methodological approach for communication and health - DOI: 10.3395/reciis.v3i3.280en - Inesita Soares de Araújo (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This article discusses ideas on context, mediation and production of meanings, in light of the methodology practiced by the Communication and Health Research Lab - Laces. From its theoretical grounds and its researches, granting special attention to the methods used, this paper contributes, clarifies and exemplifies the concepts of place of speech, hybridism, center and periphery of discourse, discursive competition, discursive community and place of dialogue. Assuming the process that produces realities is interstitial, since it takes place in the articulation (tense or synergetic) of two or more realities and that this articulation is a product and produces appropriation processes, this paper advocates that methods present nowadays in the communication field cannot grasp the multiple dimensions of the research object, formed basically by flows and relations. In contrast, it mentions researches that have innovated in methodology, testing a combination of procedures or making use of references and procedures that aren't typically used as a research method.